SP Mega Mariharta Staff Management System and Dynamic QR Code Attendance System with Role Based Access Control - Panjacharam, Eswarie; Dr. Nur Ziadah Binti Harun (Applied Information Technology And Computer Science, 2025)
This project addresses the inefficiencies in traditional staff attendance systems by implementing a modern solution at SP Mega Mariharta. The system is proposed to solve the current manual attendance tracking which is prone to errors and lacks real-time monitoring capabilities. The system incorporating role-based access control and dynamic QR codes where the employees will use a web-based system to generate dynamic QR codes for daily check-ins, enhancing security and convenience. Administrators can manage access rights dynamically based on roles, ensuring data integrity and compliance. Expected outcomes include improved accuracy, efficiency, and transparency in attendance management, benefiting both staff and management.